2010
DOI: 10.1007/s10750-010-0442-1
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat–zooplankton relationship in extensive macrophyte vegetations of eutrophic clear-water ponds

Abstract: The influence of different macrophyte taxa or growth forms on biological and environmental variables is often analysed in one-lake studies. However, the unique combination of non-vegetational characteristics of a waterbody, i.e. its site identity, can be an influential factor in itself, shaping the measured parameters irrespective of the presence or absence of certain macrophyte species. In this situation, the relative strengths of all factors can be determined best in a study that explicitly accounts for diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 60 publications
0
20
1
3
Order By: Relevance
“…These results can mostly be explained by macrophytes habitat and morphology present in this shallow reservoir, which both macrophytes are floating perennial aquatic plant or free-floating perennial or annual macrophytes. The number of planktonic taxa found was higher than those pointed by Albertoni et al (2007) and lower than found by Onsem et al (2010).…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…These results can mostly be explained by macrophytes habitat and morphology present in this shallow reservoir, which both macrophytes are floating perennial aquatic plant or free-floating perennial or annual macrophytes. The number of planktonic taxa found was higher than those pointed by Albertoni et al (2007) and lower than found by Onsem et al (2010).…”
Section: Discussioncontrasting
confidence: 67%
“…Macrophyte stands may also be responsible for the existence or the amplification and compression of vertical gradients in physical-chemical parameters such as light and oxygen availability. This may increase the faunal diversity over the whole water column (Onsem et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide range of the zooplankton diversity index in the investigated ponds reflected a high level of habitat heterogeneity. Macrophytes in ponds, which can overgrow the whole column of water or occur in patches, can be a home for a variety of zooplankters, both macrophyte-associated as well as migrating pelagic species, as stated by van Onsem et al (2010). Thus, a great range of zooplankton diversity was also ascertained for small water bodies in an agricultural landscape.…”
Section: Discussionmentioning
confidence: 99%
“…They affect the habitat of the plankton community, particularly as a food source directly or indirectly through the periphyton growing on the macrophytes. Macrophyte species have specific and divergent traits that result from details in plant architecture, allelopathic activity, palatability for herbivores and association with certain organisms that may attract or repel zooplankton species (Van Onsem et al 2010). The micro-invertebrate community associated to macrophytes consists of planktonic, phytophylus and micro-faunal species (Zrum & Hann 1997).…”
Section: Introductionmentioning
confidence: 99%